Pandangan Alkitab Mengenai Karakteristik Kepemimpinan Berdasarkan Kisah Para Rasul 20:17-38 - Lumaya, Marlon (STT INDONESIA MANADO, 2021)
Frustration is the single greatest enemy of leadership in the 21st century. Be it religious leaders, politicians or leaders, all struggle against the lack of initiative and personal responsibility that generally erodes today's work ethic. Those who continue to apply leadership that failed in the past will carry past failures into the present. The researcher formulates the problem to be studied, namely the biblical view of leadership characteristics based on Acts 20:17-38. Luke provides insight into the inner dynamics of Christian leadership in his account of Paul's conversations with ministers, described as an exemplary Christian leader. Every detail of this talk is rich with significance for leaders.